Does corporate governance affect dividend policy in India? Firm-level evidence from new indices. Issue 9 (29th July 2019) - Pahi, Debasis; Yadav, Inder Sekhar
Abstract : Purpose: The purpose of this paper is to investigate the nexus between corporate governance and dividend policy of listed Indian firms. Design/methodology/approach: Using new corporate governance stipulations, five new indices were constructed, namely, overall board governance index, board structure index, audit committee index, compensation committee index and nomination committee index. Using the newly developed indices, disclosure index and different firm-specific control variables, different panel Logit and Tobit regression models were estimated for 482 non-financial and non-utility listed firms during 2006–2017. Also, before the econometric analysis, mean difference test was conducted to examine the differences in dividend behaviour and corporate governance practices during pre- and post-Companies Act, 2013 and between payers and non-payers. Findings: The overall evidence suggests that the firms having stronger corporate governance tend to pay higher dividends suggesting that the firm's propensity to pay dividends increases with the improvement in corporate governance standards. Among the corporate governance indices board structure, audit committee and disclosure norms show a significant and positive relationship, whereas compensation committee and nomination committee show a positive but insignificant relationship with dividend policy. Control variables mostly had the expected impact on the dividends of the firms. Practical implications: This study suggests that the establishment of the strong and effective corporate governance system is desirable to mitigate the agency conflicts between managers and shareholders and limit managers' opportunistic behaviour in dividend payout policy. Originality/value: This study is one of the latest studies to use several newly constructed indices on corporate governance mechanism based on new stipulations which bring new evidence on their specific impact on the dividend policy for an emerging market economy like India.